Gut Microbiota and Serum Metabolic Signatures of High-Fat-Induced Bone Loss in Mice - Lu, Lingyun; Tang, Mengjia; Li, Jiao; Xie, Ying; Li, Yujue; Xie, Jinwei; Zhou, Li; Liu, Yi; Yu, Xijie (Frontiers in Cellular and Infection Microbiology, 2021)
Background: Accumulating evidence indicates that high-fat diet (HFD) is a controllable risk factor for osteoporosis, but the underlying mechanism remains to be elucidated. As a primary biological barrier for nutrient entry into the human body, the composition and function of gut microbiota (GM) can be altered rapidly by HFD, which may trigger abnormal bone metabolism. In the current study, we analyzed the signatures of GM and serum metabolomics in HFD-induced bone loss and explored the potential correlations of GM and serum metabolites on HFD-related bone loss. Methods: We conducted a mouse model with HFD-induced bone loss through a 12-week diet intervention. Micro-CT, Osmium-μCT, and histological analyses were used to observe bone microstructure and bone marrow adipose tissue. Quantitative Real-Time PCR was applied to analyze gene expression related to osteogenesis, adipogenesis, and osteoclastogenesis. Enzyme-linked immunosorbent assay was used to measure the biochemical markers of bone turnover. 16s rDNA sequencing was employed to analyze the abundance of GM, and UHPLC-MS/MS was used to identify serum metabolites. Correlation analysis was performed to explore the relationships among bone phenotypes, GM, and the metabolome. Results: HFD induced bone loss accompanied by bone marrow adipose tissue expansion and bone formation inhibition. In the HFD group, the relative abundance of Firmicutes was increased significantly, while Bacteroidetes, Actinobacteria, Epsilonbacteraeota, and Patescibacteria were decreased compared with the ND group. Association analysis showed that thirty-two bacterial genera were significantly related to bone volume per tissue volume (BV/TV). One hundred and forty-five serum metabolites were identified as differential metabolites associated with HFD intervention, which were significantly enriched in five pathways, such as purine metabolism, regulation of lipolysis in adipocyte and cGMP-PKG signaling pathway. Sixty-four diffiential metabolites were matched to the MS2 spectra; and ten of them were positively correlated with BV/TV and five were negatively correlated with BV/TV. Conclusions: These findings indicated that the alternations of GM and serum metabolites were related to HFD-induced bone loss, which might provide new insights into explain the occurrence and development of HFD-related osteoporosis. The regulatory effects of GM and metabolites associated with HFD on bone homeostasis required further exploration.